2005
DOI: 10.1038/sj.cr.7290355
|View full text |Cite
|
Sign up to set email alerts
|

Global human genetics of HIV-1 infection and China

Abstract: Genetic polymorphisms in human genes can influence the risk for HIV-1 infection and disease progression, although the reported effects of these alleles have been inconsistent. This review highlights the recent discoveries on global and Chinese genetic polymorphisms and their association with HIV-1 transmission and disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…This allele results in a truncated protein of CCR5, which is retained in the endoplasmic reticulum instead of being expressed on the cell surface, subsequently blocking the entry of HIV-1 to the cells (Benkirane et al, 1997;Meyer et al, 1997;Michael et al, 1997;Theodorou et al, 1997;Venkatesan et al, 2002). Compared with the high frequency of 0.1 of CCR5-D32 allele in Caucasians, it is extremely low in Asians and Africans, indicating genetic heterogeneity of HIV-1 infection in different races (Galvani and Novembre, 2005;Zhu et al, 2005). A HIV-1-infected person with acute myeloid leukemia was transplanted with allogeneic CCR5-D32 +/+ homozygous stem cells and showed successful reconstitution of CD4 + T cells at the systemic level without any evidence of HIV-1 infection for more than 3.5 years after discontinuation of antiretroviral therapy (Allers et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…This allele results in a truncated protein of CCR5, which is retained in the endoplasmic reticulum instead of being expressed on the cell surface, subsequently blocking the entry of HIV-1 to the cells (Benkirane et al, 1997;Meyer et al, 1997;Michael et al, 1997;Theodorou et al, 1997;Venkatesan et al, 2002). Compared with the high frequency of 0.1 of CCR5-D32 allele in Caucasians, it is extremely low in Asians and Africans, indicating genetic heterogeneity of HIV-1 infection in different races (Galvani and Novembre, 2005;Zhu et al, 2005). A HIV-1-infected person with acute myeloid leukemia was transplanted with allogeneic CCR5-D32 +/+ homozygous stem cells and showed successful reconstitution of CD4 + T cells at the systemic level without any evidence of HIV-1 infection for more than 3.5 years after discontinuation of antiretroviral therapy (Allers et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, a study on one patient showed that HIV-1 infected patient treated with CCR5 Δ32/Δ32 stem cell transplantation reconstituted CD4 + T cell and remained without viral rebound after treatment [8,9]. However, a survey in a Chinese population found no homozygous CCR5 Δ32 individuals, and only about 0.36% (5 of 1406) were carriers of the CCR5 Δ32 allele [10,11]. Other CCR5 alleles and one CCR2 variant have shown varying levels of association with risk of HIV transmission and disease progression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple sexual exposures, some individuals remain seronegative, whereas some infected individuals become symptomatic within 2-3 years while others remain asymptomatic for more than 10-15 years [Fauci, 1996;Fauci et al, 1996;O'Brien et al, 2000]. Studies in the past few years have demonstrated that innate immunity including genetic polymorphism in host genes can affect the risk of HIV-1 infection and disease progression, although the effect of these alleles has been inconsistent [Zhu et al, 2005]. Evidence of strong epidemiological associations between cytokines and HIV disease progression has been limited and in some cases inconsistent across studies [Marmor et al, 2006].…”
Section: Introductionmentioning
confidence: 99%